Emerging roles for the influenza A virus nuclear export protein (NEP). - Duncan Paterson; Ervin Fodor (PLoS Pathogens, 2012)
Influenza virus is a major human and animal pathogen causing seasonal epidemics and occasional pandemics in the human population that are associated with significant morbidity and mortality. Influenza A virus, a member of the orthomyxovirus family, contains an RNA genome with a coding capacity for a limited number of proteins. In addition to ensuring the structural integrity of virions, these viral proteins facilitate the replication of virus in the host cell. Consequently, viral proteins often evolve to perform multiple functions, the influenza A virus nuclear export protein (NEP) (also referred to as non-structural protein 2, or NS2) being an emerging example. NEP was originally implicated in mediating the nuclear export of viral ribonucleoprotein (RNP) complexes, which are synthesized in the infected cell nucleus and are assembled into progeny virions at the cell membrane. However, since then, new and unexpected roles for NEP during the influenza virus life cycle have started to emerge. These recent studies have shown NEP to be involved in regulating the accumulation of viral genomic vRNA and antigenomic cRNA as well as viral mRNA synthesized by the viral RNA-dependent RNA polymerase. Subsequently, this regulation of viral RNA transcription and replication by NEP was shown to be an important factor in the adaptation of highly pathogenic avian H5N1 influenza viruses to the mammalian host. Unexpectedly, NEP has also been implicated in recruiting a cellular ATPase to the cell membrane to aid the efficient release of budding virions. Accordingly, NEP is proposed to play multiple biologically important roles during the influenza virus life cycle.